Analisis Penyelesaian Hubungan Kerja yang Terjadi di Perusahaan Industri Perhotelan - Alden Nelson; Erika Chanada; Ferdianto Riady; Kevin Salim; Vincent Nicholas (Jurnal Mirai Management, 2023)
Abstract In a job, there is a working relationship between the employer and the worker. The working relationship between employers and workers does not always work well and harmoniously. In the employment relationship agreement, disputes or conflicts may arise between employers and workers. Labor relations disputes can be complex problems and obstacles that need to be handled properly. The object in this study is a company which is engaged in tourism and hospitality. The type of research used is qualitative and data collection methods with secondary data. The results of the study show that dispute resolution is carried out in court. The judge's decision stated that the demotion carried out by the company was not in accordance with procedures and had no reason. The company is also based on the approved work agreement must carry out its obligations, namely paying off employee rights. Keywords: Employment relations, disputes, employers, workers